Modification of the association between antipsychotic treatment response and childhood adversity by MMP9 gene variants in a first-episode schizophrenia cohort. (April 2018) - McGregor, Nathaniel; Thompson, Nicole; O'Connell, Kevin Sean; Emsley, Robin; van der Merwe, Lize; Warnich, Louise
Abstract: Antipsychotics remain the most effective, and wide used option for ameliorating the symptoms of schizophrenia. However, inter-individual differences in treatment outcome are vast and suggest a role for genetic and environmental factors in affording favourable outcomes. A notable epigenetic relationship which has gained considerable traction in recent literature is the way in which the severity of childhood trauma can modify associations seen between genetic variation and antipsychotic treatment response. A potential mechanism of action which may facilitate this relationship is synaptic plasticity. This study investigated the role of variants in matrix metallopeptidase 9 ( MMP9 ), a gene involved in synaptic plasticity, with treatment outcome considering the severity of childhood trauma as an interacting variable. The cohort comprised South African first episode schizophrenia patients treated with a single injectable antipsychotic, flupenthixol decanoate, monitored over 12 months. Relationships between novel and previously described variants, and haplotypes, with antipsychotic treatment response were found to be modified when considering childhood trauma as an interacting variable. This study provides the first evidence for the involvement of polymorphisms within MMP9 and the severity of childhood trauma in antipsychotic treatment response, and warrants further investigation into the role gene-environment interactions may play in the betterment of antipsychotic treatment strategies. Highlights: Variants within matrix metallopeptidase 9 ( MMP9 ) are association with antipsychotic treatment response. The relationship between childhood trauma and antipsychotic treatment response is modified by variants in MMP9. The severity of childhood trauma is associated with antipsychotic treatment response.